Backup system to the global positioning system as a risk mitigation factor in South Africa - Ntuli, Somangamane Benjamin (My University, 2014)
Since South Africa's acceptance back into the international community in 1994, sanctions and disinvestments have ceased. Globalisation has introduced various technological systems such as the global positioning system (GPS) into the Republic of South Africa (RSA). Despite the many advantages of the GPS, it also poses certain threats such as linked services. A number of countries are engaged in finding a possible solution to this problem. As South Africa also uses the system, the purpose of the research study was to establish whether the country has a backup to mitigate risks to the GPS services. To arrive at findings, a Critical Social Science (CSS) approach was applied. This approach led the researcher to use the Mixed Methods of Research. A case study was drawn from a sample of participants working in the defence and security environment. The study paid particular focus on South African constitutional imperatives with reference to the defence and security of the country from a national security policy viewpoint. The researcher moved from an international to a national posture. He revisited the South African legal framework of national security policies and proceeded to locate the implications of the threats to GPS- linked services to South Africa and the African continent. These threats include selective availability, jammers, denial of service attacks and natural degradation. The report confirms the existence of such threats and explains how other countries are dealing with them. The report also identifies additional challenges within the RSA and provides possible solutions to the vexing problem of GPS threats in the RSA.